A influência de fatores macroeconômicos na sensibilidade do investimento e do caixa ao fluxo de caixa nas empresas brasileiras - Lilian Marques Nagem (2014)
The Cash-Flow sensitivity of investment, Cash, and Cash and Debt models have been discussed for years. In Brazil, the application of these models has presented results that are contradictory and opposing to the theory, raising the question of why there is such difference. Based on articles such as the ones from Allayannis and Mozumdar (2004) and Almeida, Campello and Weisbach (2004), this dissertation seeks to explain the behavior of the sensitivity models through macroeconomic factors. The data from companies traded on the Stock Market of São Paulo from 2000 to 2012 has been used. The original models were applied and analyzed, and macroeconomics variables were inserted in posterior regressions in order to verify their significance and influence in the results. The insertion of macroeconomics variables led to an econometric improvement of the models and to results that were better suited to the original theory. Furthermore, it was possible to make some interesting assumptions such as the significance of the variable balance of financing directed to corporations in Brazil on the sensitivity of the restricted companies. The Long Term Interest Rate also seemed to interfere directly in the definition of business investment. Finally, the Brazil Risk appears to be a relevant factor in the definition of the sensitivity of investment of all companies. In general, the present work reinforced the need to insert macroeconomic aspects in the analysis of the sensitivity of companies.